The human translator in the 2020s - Massey, Gary; Huertas-Barros, Elsa 1984-; Katan, David (Routledge, 2023)
"Has the language industry of the 21st century been racing ahead of the translation profession and leaving translators behind? Or are translators adapting to new sociotechnical realities and societal demands, and if so, how? The chapters in this volume seek to shed light on the profiles and position of human translators in the current decade. This collection draws together the work of leading authors to reflect on the constantly evolving lang industry. The eight chapters present new perspectives on, and concepts of, translation in a digital world. They highlight the shifts taking place in the sociotechnical environment of translation and the need to address changing buyer needs and market demands with new services, profiles and training. In doing so, they share a common focus on the added value that human translators can and do bring to bear as adaptive, creative, digitally literate experts. Addressing an international readership, this volume is of interest to advanced students and researchers in translation and interpreting studies, and professionals in the global language industry"--
This volume originated from the panel on Living Translation in Transition: The Human Translator in the Next Decade, which took place at the 9th EST Congress: Living Translation - People, Processes, Products in Stellenbosch, South Africa, on 12 September 2019
Keywords: Prognose 2020-2030; Berufsbild; Ausbildung; Technische Innovation; Übersetzer; Translating and interpreting / Technological innovations / Congresses; Translators / Training of / Congresses; Translating and interpreting / Technological innovations; Translators / Training of; Conference papers and proceedings; Konferenzschrift -- 12.09.2019 -- Stellenbosch, South Africa